Geological position, mineral assemblages and contamination of granitic pegmatites in the Moldanubian Zone, Czech Republic; examples from the Vlastejovice region - Novak,M.; Kadlec,T.; Gadas,P. (Journal of Geosciences, 2013)
Three groups of pegmatites distinct in their geological position, age, internal structure, mineral assemblages and chemical composition of minerals (tourmaline, amphibole, garnet, and biotite) were distinguished in the Vlastejovice region, Moldanubian Zone: a) tourmaline-bearing pegmatites (Qz + Kfs + Pl + Bt + Ms + Tur) enclosed in the pre-Variscan orthogneiss, b) contaminated amphibole-bearing pegmatites (Pl + Qz + Amp + Kfs + fluorite + allanite) hosted by the Fe-skarn, and c) tourmaline-bearing pegmatites cutting paragneisses (Qz + Kfs + Pl + Bt + Ms + Ab + Tur + Grt) and the Fe-skarn (Qz + Kfs + Pl + Bt + Tur ± Ab, Amp, Grt, elbaite). The pegmatites enclosed in the orthogneiss show simple internal structure and mineral assemblages, low degree of tectonometamorphic overprint. The amphibole-bearing pegmatites, likely anatectic and related to the Variscan MP-HT regional metamorphism, are spatially restricted to the Fe-skarn body and highly variable in shape, size, effects of in situ contamination by Ca, Fe ± F and REE from the host Fe-skarn, and degree of hydrothermal overprint.The tourmaline-bearing pegmatites related to the Variscan magmatic event cut different rocks (paragneisses, Fe-skarn bodies) and belong to the Moldanubian rare-element pegmatite province. They show distinct degree of textural differentiation, geochemical fractionation and external contamination by Ca and/or Fe (Ca,Fe-rich Al-poor tourmalines) higher in the less evolved pegmatite bodies in the Fe-skarn. The tourmaline-bearing pegmatites were evidently generated from the granite-pegmatite body in the footwall contact of the Fe-skarn. Degrees of the textural differentiation and geochemical fractionation of the individual tourmaline-bearing pegmatites are comparable to those of the respective parts of the parental footwall granite-pegmatite body. This observation seems consistent with the model of sequential derivation of pegmatite melts from evolving parental granite. Primitive to highly evolved and usually B-rich pegmatites originated during the Variscan orogeny from the MP (˜0.6-0.7 GPa) to the LP conditions (˜0.2 GPa), and manifest that formation of various granitic pegmatites was an integral part of the tectonomagmatic evolution of the region.
Keywords: tourmaline; granitic pegmatites; Fe-skarn; Vlastejovice; Moldanubian Zone